Drug-Resistant Salmonella typhi in Pakistan. (January 2020) - Petrin, Christine E.; Steele, Russell W.; Margolis, Elizabeth A.; Rabon, Justin M.; Martin, Holly; Wright, Alexandra
Enteric fever (formerly typhoid fever) is a bacterial illness caused by fecal-oral transmission of Salmonella typhi or paratyphi . In early 2018, an outbreak of Salmonella typhi resistant to third-generation cephalosporins, ampicillin, ciprofloxacin, trimethroprim-sulfamethoxazole, and chloramphenicol was reported in Pakistan. This strain, termed "extensively resistant typhi, " has infected more than 5000 patients in endemic areas of South Asia, as well as travelers to and from these areas, including 5 cases in the United States. We present the case of one such child who developed extensively resistant enteric fever during a recent visit to Pakistan and required broader antimicrobial treatment than typically required. Clinicians should be aware that incoming cases of enteric fever may be nonsusceptible to commonly recommended antibiotics and that extensively resistant typhi requires treatment with carbapenems such as meropenem or azithromycin.